Las Artes Plásticas como medio articulador del currículo escolar - Fernández Zamora, Alba; Angulo Hernández, Ligia (Revista Electrónica Educare, 2007)
This article recounts a teacher’s experience who integrates the curriculum, through the correlation of elements of plastic art with other subjects such as Math, Science, Social Studies and Spanish. This experience was developed in a Costa Rican rural school.